IRIDODIAGNOSIS AND ITS VALUE IN THE DIAGNOSIS OF SUDDEN DEATH (World Bulletin of Public Health, 2024)
The aim of this study was to use additional expert criteria in the diagnosis of sudden death by iridodiagnostic methods. Radial iris type is more common in the corpses of persons who died prematurely as a result of cardiovascular diseases: ischemic heart disease (36.8%), myocardial infarction (23.7%), hypertension, atherosclerosis (32.6%). In forensic medical examination in determining the main cause of sudden death iridodiagnostic methods are one of the main diagnostic methods, as this method helps to increase the objectivity and evidentiary value of forensic medical conclusions.
Keywords: Iridodiagnostics; sudden death; forensic medicine